MENANGKAP PESAN TUHAN: URGENSI KONTEKSTUALISASI ALQURAN MELALUI HERMEUNETIKA - Arrauf, Ismail Fahmi; Miswari, Miswari (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2018)
This article aims to explore hermeneutical thinking of contemporary Muslim thinkers. They are Fazlur Rahman, Nasir Hamid Abu Zayd, Mohammad Arkoun, Khaled Abou el-Fadl. These thinkers were greatly influenced by Western hermeneutical thinkers such as F. Sheiermacher, Wilhelm Dilthey, Martin Heidegger, Rydolf Bultmann, Hans-George Gadamer, Betti, Jurgen Habermas and Paul Ricoeur. The motivation of Muslim thinkers to use the hermeunetic approach developed by Western thinkers to reconstruct the meaning of the Qurâan was because they saw the initial motivation for the birth of hermeunetics from Western thinkers was because they wanted to reconstruct the Bible. The Quran and allegory are the same as the scriptures. The aspect that most influences Muslim thinkers in Western hermeunetic thinking towards the Quranic hermeneutics that they argue is the importance of reviewing the socio-historical descent of the Qurâan in order to contextualize the Qurâan. Between humans and the Qurâan that has been made throughout history by various schools and religious authorities. With hermeneutics, the Quran wants to be returned to humanity as a powerful text for every situation, condition and age.